Answer:
t
=
r
s
−
2
r
x
Step-by-step explanation:
Brainliest?
Answer:
Inverse Function: f^-1(x) = 9/4x + 9
Step-by-step explanation:
To find the inverse function we can interchange the position of the variables x and y, and then solve for y;
y = 4/9x - 4 => x = 4/9y - 4,
x = 4/9y - 4,
4/9y = x + 4,
y = 9/4x + 9/4(4),
y = 9/4x + 9/ f^-1(x) = 9/4x + 9
Answer:
Should be 5 1/2 if thats on there
Step-by-step explanation:
u take 11/2 and take out the 1 u get 10/2 so u cut 10 in half get 5 then add the one and make it 5 1/2
The correct answer is: 3) " x ; 1/2" .
_____________________________________________________
Explanation:
_____________________________________________________
Question 1)
g [ f(x) ] = ? ;
→ Given: " f(x) = 1/3 x " ;
→ Given: " g(x) = 3x " ;
__________________________________
g [ f(x) ] = g(1/3 x) = 3(1/3 x) = 1x = "x" .
__________________________________
Question 2)
g [ f(1/2) ] = ? ;
__________________________________
→ Given: " f(x) = 1/3 x " ;
→ f(1/2) = (1/3) * (1/2) = (1*1) / (3*2) = (1/6) ;
→ g [ f(x) ] =
g(1/6) = 3* (1/6) = (3/1) * (1/6) = (3*1) / (1*6) = 3/6 = (3÷3) / (6÷3) = " 1/2 " .
___________________________________________________________
Answer:
68
Step-by-step explanation:
all explanation you need in the page above
brainliest please